Microplastic-induced NAFLD: Hepatoprotective effects of nanosized selenium - Qi Shen; Yun Jie Liu; Tian Tian Qiu; San Loon k; DongHai Zhou (Ecotoxicology and Environmental Safety, 2024)
Polystyrene microplastics (MPs) are persistent environmental pollutants commonly encountered in daily human life. Numerous studies have demonstrated their ability to induce liver damage, including oxidative stress, inflammation, and lipid accumulation. However, limited information exists regarding preventive measures against this issue. In our study, we investigated the potential preventive role of selenium nanoparticles (YC-3-SeNPs) derived from Yak-derived Bacillus cereus, a novel nanobiomaterial known for its antioxidant properties and lipid metabolism regulation. Using transcriptomic and metabolomic analyses, we identified key genes and metabolites associated with oxidative stress and lipid metabolism imbalance induced by MPs. Upregulated genes (Scd1, Fasn, Irs2, and Lpin) and elevated levels of arachidonic and palmitic acid accumulation were observed in MP-exposed mice, but not in those exposed to SeNPs. Further experiments confirmed that SeNPs significantly attenuated liver lipid accumulation and degeneration caused by MPs. Histological results and pathway screening validated our findings, revealing that MPs suppressed the Pparα pathway and Nrf2 pathway, whereas SeNPs activated both pathways. These findings suggest that MPs may contribute to the development of nonalcoholic fatty liver disease (NAFLD), while SeNPs hold promise as a future nanobio-product for its prevention.